2010
DOI: 10.2165/11538510-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cilnidipine on Normal to Marginally Elevated Urine Albumin-Creatinine Ratio in Asymptomatic Non-Diabetic Hypertensive Patients

Abstract: The present study demonstrated that cilnidipine reduced UACR in hypertensive patients with normal to marginally elevated UACR independent of its BP-lowering effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In addition to studies on microalbuminuria reduction, however, studies focusing on the reduction of normal to high-normal UACR values using drugs are also important. Our recent study clearly demonstrated that cilnidipine, an L-and N-type calcium channel blocker, reduced not only microalbuminuria but also normal to high-normal levels of UACR (45). Further studies on high-normal UACR reduction using various series of drugs are essential.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to studies on microalbuminuria reduction, however, studies focusing on the reduction of normal to high-normal UACR values using drugs are also important. Our recent study clearly demonstrated that cilnidipine, an L-and N-type calcium channel blocker, reduced not only microalbuminuria but also normal to high-normal levels of UACR (45). Further studies on high-normal UACR reduction using various series of drugs are essential.…”
Section: Discussionmentioning
confidence: 85%